C1QBP Promotes Homologous Recombination by Stabilizing MRE11 and Controlling the Assembly and Activation of MRE11/RAD50/NBS1 Complex - Bai, Yongtai; Wang, Weibin; Li, Siyu; Zhan, Jun; Li, Hanxiao; Zhao, Meimei; Zhou, Xiao Albert; Li, Shiwei; Li, Xiaoman; Huo, Yanfei; Shen, Qinjian; Zhou, Mei; et al. (Molecular cell, 2019)
MRE11 nuclease forms a trimeric complex (MRN) with RAD50 and NBS1 and plays a central role in preventing genomic instability. When DNA double-strand breaks (DSBs) occur, MRN is quickly recruited to the damage site and initiates DNA end resection; accordingly, MRE11 must be tightly regulated to avoid inefficient repair or nonspecific resection. Here, we show that MRE11 and RAD50 form a complex (MRC) with C1QBP, which stabilizes MRE11/RAD50, while inhibiting MRE11 nuclease activity by preventing its binding to DNA or chromatin. Upon DNA damage, ATM phosphorylates MRE11-S676/S678 to quickly dissociate the MRC complex. Either excess or insufficient C1QBP impedes the recruitment of MRE11 to DSBs and impairs the DNA damage response. C1QBP is highly expressed in breast cancer and positively correlates with MRE11 expression, and the inhibition of C1QBP enhances tumor regression with chemotherapy. By influencing MRE11 at multiple levels, C1QBP is, thus, an important player in the DNA damage response. [Display omitted] •C1QBP stabilizes the MRE11 protein by forming the MRC complex with MRE11/RAD50•C1QBP inhibits MRE11 exonuclease activity by preventing its binding to DNA•Appropriate C1QBP levels are essential for genomic stability and DNA repair The MRE11/RAD50/NBS1 (MRN) complex plays a critical role in the initial processing of DNA double-strand breaks. Bai et al. show that C1QBP functions as a molecular sponge, which maintains MRE11 protein stability, while controlling the assembly and activation of the MRN complex for efficient DNA damage repair.